2006
DOI: 10.1007/s00464-005-0798-x
|View full text |Cite
|
Sign up to set email alerts
|

Technical feasibility of laparoscopic Finney pyloroplasty examined in a canine model

Abstract: The efficacy of laparoscopic surgery in the treatment of chronic duodenal ulcer has been demonstrated using minimally invasive approaches. This study aimed to evaluate the technical feasibility of laparoscopic Finney pyloroplasty in six dogs. Under laparoscopic guidance, the anastomosis was created using mechanical devices (n = 3) and combining a linear stapler device and intracorporeal suturing (n = 3). The operative time and complications were recorded. Evaluation of the anastomosis included studies of intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Recent studies reported the feasibility of LFP in a canine model, which strongly suggests applicability to human gastrointestinal surgery since canine and human anatomy in this region is similar (17). Sánchez-Margallo et al evaluated the technical feasibility of LFP in six dogs and successfully completed all the operations laparoscopically and postoperative studies assessed the correct function of the anastomosis (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported the feasibility of LFP in a canine model, which strongly suggests applicability to human gastrointestinal surgery since canine and human anatomy in this region is similar (17). Sánchez-Margallo et al evaluated the technical feasibility of LFP in six dogs and successfully completed all the operations laparoscopically and postoperative studies assessed the correct function of the anastomosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…This procedure, with an open approach, is in fact undertaken in cases of benign GOO, and is only rarely performed in the emergency setting since it is more technically challenging than the Heineke-Mikulicz pyloroplasty (20)(21)(22)(23). FP can be used particularly when the site of the perforation is too wide and located in D2, to ensure good caliber of the pylorus when no healthy tissue around the ulcer can provide good closure of the duodenal defect (18,24). As this is a single case report, further studies are required to define the long-term outcomes and/or compare LS to open surgery in perforated DU with GOO.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in our experience, surgeons who want to introduce minimally invasive technologies into their clinical practice need to develop special skills using animal laboratories or training models [38] that closely resemble human conditions [39]. NOTES transvaginal nephrectomy remains a technically demanding procedure because of the lack of adequate instruments and surgical expertise for performing safe and effective dissection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we should consider a variety of ethical and technical considerations regarding the use of investigational models and the design of original learning programs in minimally invasive surgery, in order to achieve introduction of the most recent minimally invasive techniques into clinical situations [24,[36][37][38][39]. Usually, experimental studies in NOTES nephrectomy have used normal pigs [2,10,12], but previous studies pointed out the potential complications when using the swine model [1].…”
Section: Discussionmentioning
confidence: 99%
“…9,10,13,14,18 With the special ethical and scientific considerations, regarding the use of experimental models and through the design of novel minimally invasive training programs, the introduction of latest minimally invasive techniques in the clinical routine is achievable. 5,[19][20][21][22][23] Traditionally, experimental studies in NOTES cholecystectomy have used normal pigs, [1][2][3][4][5] but an important limitation was encountered for translating the surgical skills acquired in normal animals to humans with symptomatic cholelithiasis. At this moment, a training model, which includes experimental physiopathology, could be needed.…”
mentioning
confidence: 99%